PENERAPAN LEARNING TECHNOLOGY SYSTEM ARCHITECTURE (LTSA) PADA MULTIMEDIA PEMBELAJARAN PERAKITAN PC - Stefanus Santosa; April Firman Daru (Program Pascasarjana Magister Teknik Informatika, Universitas Dian Nuswantoro, 2017)
Conventional learning systems still dominate the learning process at various universities. In general, learning in college lecture reflects patterns that tend in the same direction. Students the opportunity to conduct personal understanding through looping and less enrichment accommodated properly. This research tried to solved the problem. Hence, it is important to develop a teaching medium based on Learning Technology Systems Architecture (LTSA) with multimedia tutorial approach. From the test results of learning can be stated that the learning method PC assembly using multimedia-based teaching tools can support the learning that is interactive, engaging, efficient, effective, and meaningful. In addition test results also showed a significant difference compared to conventional teaching methods . Students using conventional learning systems only obtained an average score of 49.6, while students use learning system using learning tools of animation and visualization obtain an average value of 80 , 09. This suggests that the use of teaching aids by using multimedia (text, audio, video and animation) more easily understood by the students so deserves its place as a major strategy in the laboratory learning.